Multifocal Tubercular Osteomyelitis Involving Bilateral Symmetrical Second Metacarpals - Pokharel, R (Journal of Institute of Medicine Nepal, 2013)
Skeletal tuberculosis involving small bones of the hand is less common. We report a case, 6 year old boy, of bilateral symmetrical tubercular osteomyelitis of second metacarpals. He presented with gradually increasing swellings over bilateral hands over duration of one month. There was no other significant history relating to tuberculosis. Hand X-rays showed expansive lesions of bilateral second metacarpals. Thick pus and necrotic tissue was removed from both the swelling and from the bone. Presence of typical tubercular granuloma in the histopathological examination confirmed the diagnosis. The boy was treated with antitubercular drugs and improved after completion of anti-tubercular treatment. Tuberculosis can present in different ways, and should be kept as one of the possible diagnosis of several bony pathologies including metacarpals and phalanges, especially in this part of the world where tuberculosis endemic. DOI: http://dx.doi.org/10.3126/joim.v34i2.9054 Journal of Institute of Medicine August, 2012; 34:2 42-47